Effect of Arbuscular mycorrhizal fungi (AMF) and Azospirillum on growth and nutrition of banana plantlets during acclimatization phase - Villarreal Tania Carina, Medina María Emilia, Ulloa Santiago Miguel, Darwin Rueda Ortiz, Bangeppagari Manjunatha, Selvaraj Thangaswamy, Sikandar I. Mulla (Journal of Applied Pharmaceutical Science, 2016)
The effect of the co-inoculation of arbuscular mycorrhizal fungi (AMF) and Azospirillum on micro-propagated banana seedlings development during their adaptation phase was determined. At the time of transplanting, banana seedlings were inoculated with an indigenous mycorrhizal inoculum containing 10 spores/g at four doses: 0, 50, 100 and 200 g. Seventy days after fungal inoculation, 20 ml of Azospirillum in four concentrations (0, 106, 107 and 108 CFU/ml) were applied. Finally, after 98 days from the start of the experiment a second dose (40 ml) of Azospirillum in the concentrations mentioned above was inoculated. Plants were harvested 5 months after transplanting and the growth and nutritional parameters were evaluated. The analysis of the data showed that banana plants co-inoculated with 200 g of AMF and 1.5E8 CFU/ml of Azospirillum presented greater development, an increase of 7 times in height, 4 times in perimeter, 16 times in leaf area, 12 times in aerial biomass, and 8 times in root biomass relative to control plants. The results achieved were due to synergism between fungus-bacteria when inoculated at higher doses, with lower doses stimulating growth is minimal. The co-inoculation in high doses demonstrates adequate support and cooperative effect between HMA and Azospirillum crops. In addition, co-inoculation promotes optimal nutritional status because microorganisms allowed plants achieve greater absorption of phosphorus and nitrogen relative to those treated with single inoculation and the control.
Keywords: Arbuscular mycorrhizal fungi (AMF), Azospirillum, Growth, Nutrition, Banana plantlets.